How does a static measure influence passengers' boarding behaviors and bus dwell time? Simulated evidence from Nanjing bus stations. (April 2018) - Ji, Yanjie; Gao, Liangpeng; Chen, Dandan; Ma, Xinwei; Zhang, Ruochen
Abstract: Although various methods have been adopted to reliably predict bus stop dwell time, little research has explored how the adopted measures influence the efficiency of passenger boarding from the perspective of personal micro-scale behavior. Using the multi-agent concept, this study provides a simulation model based on the social force paradigm that can be applied to extract the movement characteristics of boarding passengers and calculate bus stop dwell time. For each passenger, the model incorporates five different forces that drive individual agents' boarding and alighting. Three statistical indicators (Doorway Flow Rate, Doorway Crowdedness and Waiting Entropy) are proposed to analyze the impact of static measures in different simulation scenarios. The simulation results illustrate that measures for enlarging platform areas and installing guide guardrails can observably reduce the variation in bus dwell times, but not the length of the time itself. This is because the boarding order in these measures requires a certain amount of time per passenger. However, the application of these two measures could improve the psychological experience of passenger boarding. Therefore, we recommend that transit operators in Nanjing should fully consider the gains and losses based on the implementation of the measures to make the best decision.